Análise do crescimento e da produção de ervilha torta (Pisum sativum L.) em ambiente protegido e cultivo hidropônico - Ferreira, Liana Viviam (2013)
The cultivation of edible pod peas in greenhouse and hydroponic system can be a viable alternative for obtaining high pods yield in winter and early spring crop-seasons. In addition, this crop system optimizes productive resources and causes reduced environmental impact. Currently, little information is available about edible pods pea crop, especially in greenhouse and hydroponic cultivation conditions. The adoption of this system presupposes to adequate plant density, as well as to produce knowledge and information regarding growth (dry matter production and partitioning) and yield of different genotypes. In this sense, two experiments were conducted with edible pods pea crop grown in hydroponic and greenhouse in winter/spring crop-season at the Campus of the Universidade Federal de Pelotas , in Capão do Leão, RS. The first experiment aimed to evaluate the effect of plant density on dry matter production and partitioning and yield components of edible pods pea crop 'Luana Gigante®'. Five planti densities (3.9, 4.7; 5.9, 7.8 and 11.8 plants m-2) were evaluated from May to November 2011. The second experiment aimed to characterize the growth and production dynamics of two edible pea pods genotypes ('Luana Gigante®' and 'MK10®') in a bifactorial model from May to November 2012. Genotypes composed the plots and evaluation dates composed subplots (0, 15, 30, 45, 60, 75, 95, 115 and 135 days after setting/DAS). In both experiments, biomass was quantified by dry weight of different above-ground plant organs and yield by pods fresh weight. The results obtained in the first experiment indicated that increasing of plant density in the range from 3.9 to 11.8 plants m-2 reduced linearly the growth of all organs and the individual plants pods yield. However, it increased linearly the absolute crop dry matter production and the pods yield per square meter. It did not affect the dry matter partitioning among different plant organs. The vegetative shoot plant organs were the major sinks for photoassimilates, comprising 61.5% of total plant dry matter, while the pods represented 31.7%. Among the yield components, only the number of harvested pods per plant was reduced and there were not negative effects on average pods fresh weight and the percentage of marketable pods. Therefore, we can recommend the plant density of 11.8 plants m-2 for pea crop 'Luana Gigante'. In the second experiment, it was observed that 'Luana Gigante' and 'MK10' presented a sigmoidal type plant growth curve as a function of time. MK10 presented higher vegetative shoot plant parts and crop growth than 'Luana Gigante'. 'MK10' also presented higher pods growth at 95 DAS, but both genotypes presented similar pods growth and yield at the end of the crop cycle. Pods comprised 36% and 43% of the total above-ground dry matter production, respectively, for 'MK10' and 'Luana Gigante' at the end of the crop cycle. Thus 'Luana Gigante' presents greater ability to assimilate distribution to pods growth than 'MK10'. The vegetative shoot organs are the strongest sinks for assimilates of the plant and stems are more beneficed in relation to the partition of dry matter than leaves.